Lactose-hydrolyzed milk powder: Physicochemical and technofunctional characterization. Issue 14 (26th October 2018) - Fialho, Tatiana Lopes; Martins, Evandro; Silva, Carolina Rodrigues de Jesus; Stephani, Rodrigo; Tavares, Guilherme Miranda; Silveira, Arlan Caldas Pereira; Perrone, Ítalo Tuler; Schuck, Pierre; de Oliveira, Luiz Fernando Cappa; de Carvalho, Antônio Fernandes
ABSTRACT: The objective of this work is to demonstrate the effect of operational drying parameters on the physicochemical and techno-functional properties of lactose-hydrolyzed milk powder (LHMP). LHMP showed water content superior to the control regardless of drying conditions, which is a direct result of the difficulties encountered in drying the product. For a lab-scale spray dryer, the LHMP produced at θ air, in  = 145°C and m CM  = 1.0 kg · h −1 was the only sample that met all stipulated quality parameters: water content <5% (w/w), a w  < 0.20 and luminosity value >93, particle sizes similar to control, and complete rehydration.